Investigation of quark distributions in a family of pentaquarks using the Thomas–Fermi quark model. (8th February 2021) - Giri, Mohan; Baral, Suman; Kaphle, Gopi Chandra; Dangi, Nirmal; Shiwakoti, Sudip; Bardomero, Leonardo; Lashomb, Paul; Wilcox, Walter
Abstract: Using the Thomas–Fermi quark model, a collective, spherically symmetric density of states is created to represent a gas of interacting fermions with various degeneracies at zero temperature. Over a family of pentaquarks, uudc c ̄, color interaction probabilities were obtained after averaging over all the possible configurations. Three different functions are developed for light, charm, and anti-charm quarks and are assumed to be linearly related by some proportionality constants. Interesting patterns of quark distributions are observed while analyzing the quark function consistency conditions for such constants.